ISLAMIC SPORTS MANAGEMENT AS A MEDIUM FOR DA'WAH AND MORAL DEVELOPMENT OF SANTRI AT AR-RAUDLATUL HASANAH ISLAMIC BOARDING SCHOOL MEDAN (Pena Cendekia Insani, 2026)
This study aims to analyze how sports management based on Islamic values is implemented as an instrument of da'wah bil hal (missionary by action) and a means of character building (akhlak) for students at Ar-Raudlatul Hasanah Islamic Boarding School (Pesantren) Medan. The phenomenon of moral degradation in the digital era demands that pesantren innovate development strategies that focus not only on cognitive-religious aspects but also on structured physical activities. Using a descriptive qualitative approach, data were collected through field observations, in-depth interviews with mentors and sports coordinators, and documentation studies of literature related to educational management and Islamic sports. The results indicate that sports management at Ar-Raudlatul Hasanah encompasses four main pillars: scheduling plans synchronized with prayer times, organizing human resources (coaches) as murabbi (mentors), implementing activities that maintain codes of conduct (including standardized shari'a-compliant sportswear), and supervising student behavior on the field. Sports serve as an effective medium for da'wah in internalizing transcendental values such as honesty (shiddiq), sportsmanship, discipline, and Islamic brotherhood (ukhuwah Islamiyah). These findings confirm that integrating Islamic values into sports management can transform physical activity into a holistic character-building tool, as well as a preventive solution against negative external cultural influences. This study recommends the need to strengthen digital literacy in publishing students' sports content as a broader contemporary medium for da'wah.